Wolbachia affects sleep behavior in Drosophila melanogaster. (May 2018) - Bi, Jie; Sehgal, Amita; Williams, Julie A.; Wang, Yu-Feng
Graphical abstract: Highlights: Wolbachia increased total sleep time of D. melanogaster . Wolbachia increased the sleep bouts number during night time. Wolbachia reduced arousal threshold in flies. Wolbachia alter neither circadian rhythm nor sleep homeostasis. Wolbachia increased mRNA level of genes in dopamine biosynthesis pathway. Abstract: Wolbachia are endosymbiotic bacteria present in a wide range of insects. Although their dramatic effects on host reproductive biology have been well studied, the effects of Wolbachia on sleep behavior of insect hosts are not well documented. In this study, we report that Wolbachia infection caused an increase of total sleep time in both male and female Drosophila melanogaster. The increase in sleep was associated with an increase in the number of nighttime sleep bouts or episodes, but not in sleep bout duration. Correspondingly, Wolbachia infection also reduced the arousal threshold of their fly hosts. However, neither circadian rhythm nor sleep rebound following deprivation was influenced by Wolbachia infection. Transcriptional analysis of the dopamine biosynthesis pathway revealed that two essential genes, Pale and Ddc, were significantly upregulated in Wolbachia -infected flies. Together, these results indicate that Wolbachia mediates the expression of dopamine related genes, and decreases the sleep quality of their insect hosts. Our findings help better understand the host-endosymbiont interactions and in particular the Wolbachia 's impact on behaviors, and thus on ecology and evolution in insect hosts.